Psikoedukasi Keluarga Pada Pasien Pasca Pasung Di Kabupaten Sukoharjo Propinsi Jawa Tengah - Samsul Hidayat, Ryan; , Arif Widodo, A.Kep., M.Kes (2017)
Views of people about the problems people with mental disorders is synonymous with the term "lunatic" so many people look at the negative and threatening. Label negative impact on the family or the community about people with mental disorders do not want to take care of Need an effort to increase the understanding and role of families and communities to care of patients with mental disorders by administering one psychoeducation. The purpose of this study was to find out there differences in the level of knowledge and friendly attitude in Patients Post airborne in Sukoharfo, Central Java Province. This research is quantitative with quasi-experimental approach. The study population was Sukoharfo district community numbering 43 souls in stocks. The research sample of 30 family members who were determined using purposive sampling technique. Collecting data using a questionnaire, while analyzed using t-test. Conclusion of research is a signcant difference pre test and post test knowledge and attitudes about the prevention of deprivation after getiing Psychoeducation in the family of mental patients in Sukoharjo, where the value of post tqt is higher than the pre-test. Keywords: psycho education, knowledge, attitude, family, patients stocks